The Role of Culture in Business Negotiations in South Korea - Suchanova, Anna (2025)
This bachelor’s thesis focuses on the role of culture in business negotiations in South Korea, exploring how South Korean culture affects business negotiation practices. The theory provides insights into South Korea's cultural dimensions and South Korean culture’s role in business and business negotiations. This bachelor’s thesis combines qualitative research, consisting of five interviews with Czech and South Korean professionals, and a quantitative survey among the South Korean Generation Z. Thematic analysis is used to analyze the qualitative data and descriptive statistics are used for the quantitative survey. The results indicate that although South Korean culture's role is still significant, particularly in terms of hierarchy and respect for seniority, Generation Z is reevaluating aspects such as working standards and authority. Their perspectives are shifting away from traditional views, reflecting a shift towards international openness, well-being and individualism. This bachelor’s thesis aims to provide recommendations for foreign firms to successfully engage in business negotiations in South Korea.